Vonis Mahkamah Konstitusi Mengeksaminasi Keterwakilan Perempuan - Mohamad Faisol (Jurnal Konstitusi, 2016)
The verdict imposed by the Constitutional Court in the form of revocation of some parts of General Election Rules which arrange the determination of the representative who has the rights to occupy the council seats is not a verdict which discriminates and hinders women rights to fight for occupying the council seats, but it gives them more available and egalitarian chances to female politicians. The Constitutional Court verdict also examines the political party to elect and decide the council representatives truly based on the aspect of rasionality, professionality, and any other special aspects supporting them.